Classification nanostructure multicomponent organic fat - Rashevska, Tamara (My University, 2005)
We studied nanostructure of complex organic systems fat/water/natural organic material.
Keywords: fat phase; nanostructure; nanoelements; наноструктура; жирова фаза; наноелементи; кафедра технології молока і молочних продуктів